MEXICAN BIOGEOGRAPHIC PROVINCES: PRELIMINARY SCHEME, GENERAL CHARACTERIZATIONS, AND SYNONYMIES - Morrone, Juan J.; Espinosa Organista, David; Llorente Bousquets, Jorge (Instituto de Ecología, A.C., 2002)
Although the biogeographic schemes proposed for Mexico are based on different criteria (geographic, paleontological, faunistic or floristic), their authors implicitly acknowledge that the units recognized actually represent historical entities. The development of panbiogeography and cladistic biogeography has challenged traditional classifications, by showing that some of these biogeographic units did not represent natural units. Furthermore, there have been attempts to construct ecogeographic systems, based on the assumption that biotic and abiotic factors constraint species distributions within definite areas. By synthesizing both biogeographic and ecological systems, we propose a new scheme for Mexico, where we recognize the following 14 provinces: California (northern portion of the Baja California peninsula, from Sierras of San Pedro Mártir and Juárez, extending northward along the Sierra Nevada into southwestern USA), Baja California (Baja California peninsula), Sonora (coastal areas in northwestern Mexico, from the northeastern portion of the Baja California peninsula to the Piaxtla river basin in southern Sinaloa), Mexican Plateau (central Mexico, in the states of Zacatecas, San Luis Potosí, Guanajuato, Chihuahua, Coahuila, Durango, and Nuevo Mexico, as well as small parts of Nuevo León, and Sonora, below 4,000 m altitude), Tamaulipas (coastal areas in the northern part of the Mexican Gulf, north of the Pánuco river basin), Sierra Madre Occidental (western Mexico, in the states of Chihuahua, Durango, Zacatecas, Sonora, Sinaloa, Nayarit, and Jalisco, above 1,000 m altitude), Sierra Madre Oriental (eastern Mexico, in the states of San Luis Potosí, Tamaulipas, Coahuila, Hidalgo, Nuevo León, Veracruz, Puebla, and Querétaro, above 1,500 m altitude), Transmexican Volcanic Belt (central Mexico, in the states of Guanajuato, Mexico, Distrito Federal, Jalisco, Michoacán, Puebla, Oaxaca, Tlaxcala, and Veracruz), Balsas Basin (central Mexico, in the states of Guerrero, Mexico, Jalisco, Michoacán, Morelos, Oaxaca, and Puebla, below 2,000 m altitude), Sierra Madre del Sur (south central Mexico, from southern Michoacán to Guerrero and Oaxaca, and part of Puebla, above 1,000 m altitude), Mexican Gulf (coast of the Mexican Gulf, in eastern Mexico, Belize, and northern Guatemala), Mexican Pacific Coast (western Mexico, in the Pacific coast of the states of Sinaloa, Nayarit, Colima, Jalisco, Michoacán, Guerrero, Oaxaca, and Chiapas), Yucatán Peninsula (Yucatán peninsula, in the states of Campeche, Yucatán, and Quintana Roo, below 200 m altitude), and Chiapas (southern Mexico, Guatemala, and Nicaragua, basically corresponding to the Sierra Madre de Chiapas, from 500 to 2,000 m altitude).